A New Interactive Decision Approach with Probabilistic Linguistic Data: An Application in the Academic Sector. (21st April 2022) - Ravichandran, K.S.; Krishankumar, R.; Deb, Sibnath; Pamucar, Dragan; Paul, David; Božanić, Darko
Abstract : As an innovative generalization to a linguistic term set, the probabilistic variant is gaining abundant attraction in the decision process. However, earlier studies with this variant for decision-making have not adequately explored hesitation in data articulation and interactive ranking. Driven by the claim, in this paper, a new integrated approach is put forward under the probabilistic linguistic context, which attempts to address the claims by presenting a regret/rejoice technique and an interactive WASPAS algorithm for determining the significance of factors and personalized ranking of alternatives. To test the usefulness of the approach, the online course prioritization problem based on empirical data is exemplified, and a comparison demonstrates the benefits and limitations of the proposed work.